Pengaruh Konflik Kerja Serta Tekanan Pikiran Pada Kinerja Karyawan Di PT Herculon Carpet Semarang - Suprihono Setyawan; Feti Nur Rahmawati; Budi Hartono (LPPM Universitas Sains dan Teknologi Komputer, 2020)
The purpose of this study was to determine the effect of work conflict and work stress either partially working, and the simultaneous of the employee performance at PT Herculon Carpet Semarang. This research is a descriptive quantitative study with sample 72 employee. Data collection methods used were purposive sampling. Data were analyzed with the statistical software SPSS 25. The result of the research showed that variable of work conflict influence significant positive for employee performance with thitung score amounted 4,261 > ttabel 1,995 and significant score 0,000 ˂ 0,05, variable of work stress influence significant positive for employee performance with thitung score amounted 3,215 >ttabel 1,995 and significant score 0,002 ˂ 0,05, then variable of work conflict and work stress simultant influence significant positive for employee performance Fhitung score amounted 22.044 > Ftabel 3,13 and significant score 0,000 ˂ 0,05. Result for koefisien determinasi (R2) amounted 0,390 or amounted 39%